Catalyst for Change: A Grassroots Implementation of a Residency Communication Curriculum and Resulting Culture Change - Sekar, D.R.; Dorough, R.; Watters, J. Bailey; Siropaides, C.H. (International Journal of Mass Communication, 2025)
Issue: Effective physician-patient communication is essential to end-of-life care. The teaching approach of end-of-life care communication skills has evolved over decades, from an apprenticeship model to coached practice. With this evolution of practice and teaching, also comes a continuously evolving culture that often carries remnants of prior practices. Learning complex communication skills requires a curriculum of coached practice that may be challenging to implement in settings where apprenticeship models prevail. Evidence: In this article we explore structures of change as an approach to ongoing curriculum development and associated culture change: the ‘path-goal theory’ and the ‘program development cycle.’ We explore these two models through iterations of a communication skills curriculum for internal medicine residents to understand the factors that contributed to each iterative change as well as the resulting effect on the institutional culture. We also highlight the importance of a grassroots voice in identifying tensions between culture and behaviors. Through this reflection, we show that a step-wise approach leads to incremental practice and culture change through the incremental support of all parties involved (students, educators, institution). Implications: We show that an educational intervention that challenges existing cultural norms requires stepwise implementation and adaptation as stakeholders and resources evolve. Notably, local institutional culture shapes institutional practices and, in turn, influences the teaching of communication skills. This article provides a reflection on how residency programs can find success in curricular implementation by being attuned to local resources, structure, and learner practices.